A Holocene record of ocean productivity and upwelling from the northern California continental slope. (10th March 2018) - Addison, Jason A.; Barron, John; Finney, Bruce; Kusler, Jennifer; Bukry, David; Heusser, Linda E.; Alexander, Clark R.
Abstract: The Holocene upwelling history of the northern California continental slope is examined using the high-resolution record of TN062-O550 (40.9°N, 124.6°W, 550 m water depth). This 7-m-long marine sediment core spans the last ∼7500 years, and we use it to test the hypothesis that marine productivity in the California Current System (CCS) driven by coastal upwelling has co-varied with Holocene millennial-scale warm intervals. A combination of biogenic sediment concentrations (opal, total organic C, and total N), stable isotopes (organic matter δ 13 C and bulk sedimentary δ 15 N), and key microfossil indicators of upwelling were used to test this hypothesis. The record of biogenic accumulation in TN062-O550 shows considerable Holocene variability despite being located within 50 km of the mouth of the Eel River, which is one of the largest sources of terrigenous sediment to the Northeast Pacific Ocean margin. A key time interval beginning at ∼2900 calibrated years before present (cal yr BP) indicates the onset of modern upwelling in the CCS, and this period also corresponds to the most intense period of upwelling in the last 7500 years. When these results are placed into a regional CCS context during the Holocene, it was found that the timing of upwelling intensification at TN062-O550 corresponds closely to that seen at nearby ODP Site 1019, as well as in the Santa Barbara Basin of southern California. Other CCS records with less refined age control show similar results, which suggest late Holocene upwelling intensification may be synchronous throughout the CCS. Based on the strong correspondence between the alkenone sea surface temperature record at ODP Site 1019 and the onset of late Holocene upwelling in northern California, we suggest that CCS warming may be conducive to upwelling intensification, though future changes are unclear as the mechanisms forcing SST variability may differ.